Toll-like Receptor 9 Promotes Initiation of Gastric Tumorigenesis by Augmenting Inflammation and Cellular Proliferation - Tang, Ke; McLeod, Louise; Livis, Thaleia; West, Alison C.; Dawson, Ruby; Yu, Liang; Balic, Jesse J.; Chonwerawong, Michelle; Wray-McCann, Georgie; Oshima, Hiroko; Oshima, Masanobu; Deswaerte, Virginie; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2022)
Gastric cancer (GC) is strongly linked with chronic gastritis after Helicobacter pylori infection. Toll-like receptors (TLRs) are key innate immune pathogenic sensors that mediate chronic inflammatory and oncogenic responses. Here, we investigated the role of TLR9 in the pathogenesis of GC, including Helicobacter infection. TLR9 gene expression was profiled in gastric tissues from GC and gastritis patients and from the spontaneous gp130F/F GC mouse model and chronic H felis-infected wild-type (WT) mice. Gastric pathology was compared in gp130F/F and H felis infection models with or without genetic ablation of Tlr9. The impact of Tlr9 targeting on signaling cascades implicated in inflammation and tumorigenesis (eg, nuclear factor kappa B, extracellular signal-related kinase, and mitogen-activated protein kinase) was assessed in vivo. A direct growth-potentiating effect of TLR9 ligand stimulation on human GC cell lines and gp130F/F primary gastric epithelial cells was also evaluated. TLR9 expression was up-regulated in Helicobacter-infected gastric tissues from GC and gastritis patients and gp130F/F and H felis-infected WT mice. Tlr9 ablation suppressed initiation of tumorigenesis in gp130F/F:Tlr9-/- mice by abrogating gastric inflammation and cellular proliferation. Tlr9-/- mice were also protected against H felis-induced gastric inflammation and hyperplasia. The suppressed gastric pathology upon Tlr9 ablation in both mouse models associated with attenuated nuclear factor kappa B and, to a lesser extent, extracellular signal-related kinase, mitogen-activated protein kinase signaling. TLR9 ligand stimulation of human GC cells and gp130F/F GECs augmented their proliferation and viability. Our data reveal that TLR9 promotes the initiating stages of GC and facilitates Helicobacter-induced gastric inflammation and hyperplasia, thus providing in vivo evidence for TLR9 as a candidate therapeutic target in GC.